A Multispecies Collecting Strategy for Crop Wild Relatives Based on Complementary Areas with a High Density of Ecogeographical Gaps. Issue 3 (16th June 2017) - García, Rosa M.; Parra‐Quijano, Mauricio; Iriondo, José M.
Abstract : Amidst the general concern about the need to conserve crop wild relatives (CWR) as a source of genetic diversity potentially useful in crop breeding, recent studies have assessed global gaps in CWR conservation using predictive distribution approaches. However, few options are available to downscale such studies and conduct efficient seed‐collecting expeditions in specific target areas for ex situ conservation. A new type of optimized collecting design (OCD) to determine priority areas for collecting CWR is presented to fit this purpose. The new approach is based on the principles of complementarity and ecogeographical representativeness of ex situ collections, using ecogeographical variation as a proxy for genetic diversity of adaptive value. It aims to offer a collecting strategy that captures the maximum genetic diversity of adaptive value at a minimum cost. Ninety‐eight priority species related to cereal and legume crops, selected by the Spanish National Strategy for CWR Conservation, were targeted to illustrate this approach. The analysis resulted in a ranking of 10‐ × 10‐km areas containing decreasing richness of complementary ecogeographical gaps of selected CWR taxa. The top 10 complementary areas were overlapped with the Spanish Sites of Community Importance of the Natura 2000 network to prioritize collection in areas not covered by the network, which would be more exposed to habitat destruction and other anthropic risks. This new kind of OCD allows collectors to efficiently sample nonrepresented populations of many species growing in adaptive scenarios within a relatively reduced area at the same time.